Auditory Perceptual Exercises in Adults Adapting to the Use of Hearing Aids - Karah, Hanin; Karawani, Hanin (Frontiers in Psychology, 2022)
Older adults with age-related hearing loss often use hearing aids (HAs) to compensate. However, certain challenges in speech perception, especially in noise still exist, despite today’s HA technology. The current study presents an evaluation of a home-based auditory exercises program that can be used during the adaptation process for HA use. The home-based program was developed at a time when telemedicine became prominent in part due to the COVID-19 pandemic. The study included 53 older adults with age-related symmetrical sensorineural hearing loss. They were divided into three groups depending on their experience using HAs. Group 1: Experienced users (participants who used bilateral HAs for at least two years). Group 2: New users (participants who were fitted with bilateral HAs for the first time). Group 3: Non-users. These three groups underwent auditory exercises for three weeks. The auditory tasks included auditory detection, auditory discrimination, and auditory identification, as well as comprehension with basic (syllables) and more complex (sentences) stimuli, presented in quiet and in noisy listening conditions. All participants completed self-assessment questionnaires before and after the auditory exercises program and underwent a cognitive test at the end. Self-assessed improvements in hearing ability were observed across the HA users groups, with significant changes described by new users. Overall, speech perception in noise was poorer than in quiet. Speech perception accuracy was poorer in the non-users group compared to the users in all tasks. In sessions where stimuli were presented in quiet, similar performance was observed among new and experienced uses. New users performed significantly better than non-users in all speech in noise tasks; however, compared to the experienced users, performance differences depended on task difficulty. The findings indicate that HA users, even new users, had better perceptual performance than their peers who did not receive hearing aids.